Digital Financial Literacy for Smart and Independent Families - Dewi, Yuli (Jurnal Ar Ro'is Mandalika (Armada), 2026)
The rapid advancement of digital technology has profoundly transformed financial systems worldwide, including in Indonesia. Digital financial services such as mobile banking, e-wallets, and QRIS have become integral to modern life. However, the rise in financial inclusion has not been matched by adequate financial literacy. According to the 2024 Financial Services Authority (OJK) survey, Indonesia’s financial inclusion index reached 85.1%, while financial literacy was only 49.6%. This disparity indicates that many people have access to financial services but lack sufficient understanding to use them wisely, safely, and productively. This Community Service Program (PKM) aims to improve digital financial literacy among members of the PKK women’s community at Posyandu Baronang RW 016, Beji, Depok, enabling them to become smart and independent family financial managers. The program utilized an interactive learning approach involving educational lectures, digital application demonstrations, financial management training using mobile apps, and group discussions. The results revealed a significant improvement in participants’ understanding of digital financial concepts, secure transaction practices, and household budgeting using digital tools. The activity also empowered women as financial educators within their families and communities. This initiative demonstrates that digital financial literacy plays a crucial role in enhancing family resilience and independence in the digital economy era.